The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1071/an12163
|View full text |Cite
|
Sign up to set email alerts
|

Male traits and herd reproductive capability in tropical beef cattle. 2. Genetic parameters of bull traits

Abstract: A total of 4063 young bulls of two tropical genotypes (1639 Brahman and 2424 Tropical Composite) raised in northern Australia were evaluated for a comprehensive range of production and reproduction traits up to 24 months of age. Prior to weaning, peripheral blood concentrations of luteinising hormone (LH) and inhibin were measured at 4 months of age. At weaning (6 months) blood insulin-like growth factor-1 (IGF-I) and flight time were recorded. Body composition traits of fat depth and eye-muscle area were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
59
6
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 41 publications
8
59
6
2
Order By: Relevance
“…The age of young bulls at recording was considered a covariate for SC. Details about animals, cohorts and phenotypes are described in Burns et al (), Corbet et al (), Fortes et al () Johnston et al (), and Johnston, Barwick, Fordyce, and Holroyd ().…”
Section: Methodsmentioning
confidence: 99%
“…The age of young bulls at recording was considered a covariate for SC. Details about animals, cohorts and phenotypes are described in Burns et al (), Corbet et al (), Fortes et al () Johnston et al (), and Johnston, Barwick, Fordyce, and Holroyd ().…”
Section: Methodsmentioning
confidence: 99%
“…The analysis performed was similar to those performed in previous GWAS and quantitative genetic analyses [12,29,30]. Briefly, the mixed model can be written as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Several studies state that some male reproductive traits are heritable. For instance, some authors reported that scrotal circumference (Burrow, ; Cammack, Thomas, & Enns, ; Meyer, Hammond, Parnell, Mackinnon, & Sivarajasingham, ), normal/abnormal spermatozoa rate and sperm motility, in general, have a heritability range of 0.04–0.47 in North American and European Bos Taurus breeds (Corbet et al., ; Gredler, Fuerst, Fuerst‐Waltl, Schwarzenbacher, & Sölkner, ; Kealy, MacNeil, Tess, Geary, & Bellows, ; Yilmaz, Davis, & Simmen, ). There is some information available on the relationship between andrological and spermatological examination and ageing in humans, but very few reports are available on dogs.…”
Section: Introductionmentioning
confidence: 99%